2010
DOI: 10.1016/j.actao.2010.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: Space use of Eurasian red squirrels in marginal high-elevation habitat

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 66 publications
6
46
0
Order By: Relevance
“…Animals can show high plasticity in their ranging behaviour to cope with the ecological constraints imposed in marginal habitats (Romeo et al ., ). Higher altitudes are less productive (Costin et al ., ) and, as the results here show, wombat home range increased with altitude, providing support for the hypothesis that low food availability leads to larger home range sizes in mammals (Jones, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Animals can show high plasticity in their ranging behaviour to cope with the ecological constraints imposed in marginal habitats (Romeo et al ., ). Higher altitudes are less productive (Costin et al ., ) and, as the results here show, wombat home range increased with altitude, providing support for the hypothesis that low food availability leads to larger home range sizes in mammals (Jones, ).…”
Section: Discussionsupporting
confidence: 86%
“…Field data on the movement of individuals at the range boundary are sparse (Kanda et al, 2009). However, several studies have shown that space use and movements of animals are greater in marginal habitats at the range edge (Sunde et al, 2001;Romeo et al, 2010), or on the invading front of an expanding range (Alford et al, 2009). These differences in behavioural traits might give animals in marginal populations the advantage of increased dispersal ability (Phillips, Brown & Shine, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1). This pattern has been found in plants (Volis et al 1998), insects (Otaki et al 2010), mammals (Romeo et al 2010), and birds (Sunde et al 2001).…”
Section: A Conceptual Model Based On Observed Alternatives For Intrassupporting
confidence: 54%
“…Most tree squirrels reduce home-range size when overall food abundance is high and the converse occurs when food availability is low (Lurz et al 2000;Wauters et al 2005;Romeo et al 2010).…”
Section: Methodsmentioning
confidence: 96%